أحاديث رؤية الهلال ومحاولة اكتشاف التطور في مفهومها - فردوس بن يحيى (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2005)
This is a study on the Prophetic sayings on the sighting of the moon in determining the cycle of the Muslim Hijrah calendar. It begins by comparing the mechanics of both the Hijrah and Gregorian calendars, and by examining the great strides in astronomy made by both Muslim and non-Muslim astronomers, especially in the area of crescent sighting techniques. Based on this discourse, the study argues that the Muslim lunar calendar is far more useful than the solar calendar. The study then scholarly presents the Prophet’s sayings on the subject, particularly those regarding crescent sighting, global sighting zones and witnesses of sightings. It argues that a unified global sighting zone is impossible, and that sighting claims should not contradict mathematical calculations, as pointed out by Imam Taqiyuddin As-Subki in the 12th century. Finally, the study suggests that in calculating the Muslim calendar, views from traditional opinions and current technologies, which do not contradict the Shari'ah’s principles, should continue to be considered.